Legal Responsibility for Corruption Policies in Digital-Based Local Government Goods and Services Procurement Mechanisms - Ramadhani, Syifa Utari; Bawono, Bambang Tri (Jurnal Hukum Khaira Ummah, 2025)
Policy corruption in digital-based local government procurement mechanisms is a serious threat to the integrity of governance and national development. This phenomenon specifically occurs when public regulations or policies, such as overly specific technical requirements or qualification criteria that deviate from fair procurement principles, are manipulated to benefit certain goods/services providers who have close ties with policy makers. This manipulation exploits gaps in digital systems that should be designed to increase transparency and accountability, for example by deliberately creating ambiguity in electronic auction specifications or limiting access to digital platforms for other potential providers. Therefore, the author raises the title "Legal Responsibility for Policy Corruption in Digital-Based Local Government Procurement Mechanisms". The research method uses a normative juridical approach, namely by examining primary, secondary and tertiary materials, primary legal materials consist of the 1945 Constitution, Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services and various official documents containing law, then examining secondary legal materials in the form of books, journals, articles, research reports and so on. This research uses 2 approach models, namely carried out with a Statute approach and a conceptual approach. The analysis method of this qualitative juridical research is an analysis method used to describe data comprehensively and qualitatively in the form of sentences that are coherent, orderly, logical, and effective to facilitate data interpretation and understanding of the results of the analysis, the analytical tools used in this study use the theory of legal responsibility and the theory of legal certainty The digital-based procurement mechanism for regional government goods and services is regulated by Presidential Regulation No. 12 of 2021 concerning Amendments to Presidential Regulation No. 16 of 2018 concerning Government Procurement of Goods/Services, supported by the LKPP Regulation as a technical guideline. Legal liability for corruption in digital-based regional government goods and services procurement policies, with criminal liability regulated by the Corruption Law, civil liability can be filed, and administrative sanctions are imposed in the form of a National Blacklist sanction by the LKPP.